Islamic work ethics: An appraisal of the Quranic view on work ethics - Ahmad, Shukri; Rofie, Mohamad Khadafi; Owoyemi, Musa Yusuf (Medwell Journals, 2013)
The issue of work ethics or what could be referred to as the value systems associated with work has captured the attention of scholars for some time.Scholars from the Judeo-Christian background and to a large extent, modern Western societies have contributed immensely to this field of thought.However, the fact that many other religions, societies and ethnic groups throughout the world have achieved economic prosperities and tremendous advancementsin their history shows that their contribution to this issue could also be meaningful if properly harnessed.The Islamic view of work ethics which has either been misunderstood or not widely studied in the field of organizational studies falls in this category and thus, there is a need to bring it into light in the cotemporary where Islam is now becoming a force to reckon with in many societies. Thus bearing the above in mind, this study is an analogical deduction of work ethics from the pages of the Quran.Using the method of textual analyzes, it deduced what the Quran has to say about the concept of work ethics for the Muslim and mankind at large. To fulfill its aim, the study examines some concepts through which the Quran talks about work and highlight the ethics that could be deduced from this.It starts by scanning the passages of the Quran in order to understand how it sees work and its relationship with ethics; the concept of time and how important this is as it concerns work how work is related to the concept of wealth and gaining wealth. Finally, it concludes on the note that if properly studied, the Quran is a rich fountain for ethics which are related to work and which if properly harnessed, could help the Muslims and mankind in general in overcoming the issues of corruption, exploitation and other vices which are inimical to the economic well being of the human societies.